Design and Analysis of Prosthetic Heart Valves and Assessing the Effects of Leaflet Design on the Mechanical Attributes of the Valves - Ghanbari, Jaafar; Dehparvar, Amirhossein; Zakeri, Amirhossein (Frontiers in Mechanical Engineering, 2022)
Prosthetic heart valves are commonly used a treatment for aortic valve deficiencies. The performance of these prosthetic valves should be in accordance with natural heart valve in respect to opening and closing, blood flow, and vortex formation. Theses performance parameters depend on design of leaflets and overall geometrical parameters of the valve. To better understand the effects of leaflet design on the performance of the valve, we have carried out fully coupled fluid structure interaction analyses of opening and closing of prosthetic heart valves with various leaflet designs. Maximum stress, valve opening, and flow stream pattern are obtained for different valve designs and used to assess the performance of the valves. The results show that the stress and the valve opening depend on the curvature and the inclination of the leaflets. A 3D model is designed based on the obtained results and a full FSI analysis is performed to assess its performance. The results show that the presented design gives better values for valve opening area and leaflet stresses, compared with the published data.